(untitled) (Islamic Sciences Journal, 2023)
The research deals with Qudduri’s answers to the inference of the violators with the verses of the rulings in the revocable divorce, and its impact on the family and society. Then how to treat it, and reduce it to the extent of its spread between the spouses, in terms of the legal rulings resulting from it. The jurists (may God have mercy on them), and their evidence, and discuss them to reach the most correct opinion. The most prominent findings of this study are: • Imam al-Qudduri (may God have mercy on him) attained a high scholarly status until he became the head of the school of thought in Iraq, and al-Dhabi said about him that he was called the Hanafi sheikh. • That who are the foundations upon which society and husbands are based, is the love and affection between the spouses that brings out a good generation from their home, and divorce spoils that because of the dispersal of the family, but the Shari’a permitted it for the benefit of the lack of compatibility between the spouses, and I legitimized the retroactive divorce to give the husband an opportunity to consider what he has done. • Return is obtained by word and deed, provided that the action is combined with the intention. • Witnessing the return has become necessary to preserve the limits of Allah Almighty, and to establish rights between spouses